Rules and regulations of The United Brothers' Birmingham Benefit Society (London : J.S. Forsaith & Son, Printers (T.U.), 1908)
1908 1908 1900s 18 pages 5 nights by eight o'clock, or be fined sixpence for each neglect ; and if not there by nine o'clock he shall be fined one shilling : and if he neglect to attend the whole evening, or send some competent person to do his duty, he shall be fined two shillings. He shall hold office so long as he conducts the business to the satisfaction of the members, and shall not be displaced without the consent of the majority of the members at a general summoned meeting held for that purpose. The duty of the secretary shall be to enrol members' names, book their contributions, &c.; he shall also send notice to all defaulting members to pay up their arrears, stating when they will be suspended from benefits and excluded the society, or be fined sixpence for each neglect ; the secretary to receive twopence for each notice, to be paid by the defaulting member. All notices to be printed and delivered at least seven days before the night of suspension ; the expense of printing notices to be defrayed by the secretary. N.B.— All notices to country members will be charged for postage. 5. That there be three persons chosen on the monthly meeting nights to serve the office of stewards, to be called in rotation as their names stand on the book; the call to commence at nine o'clock, commencing from the junior steward; any member refusing to serve or not answering to his name when called shall be fined sixpence, and should the call go round, those members who serve the office shall not have their fines remitted ; but the stewards who are in office are exempt from the roll call. They shall attend at the club house by eight o'clock in the evening during their being in office, or be fined sixpence for each neglect; they shall receive all moneys, and pay the same over to the treasurer, and be accountable for all deficiencies that may occur in the cash, and all bad money. No money to be taken after ten o'clock; the senior steward to act as chairman, the second as check steward, and the third to take the 345/7/2/2